Analysis of Sedimentation Types and Rates in the Waters of Tapulaga Village Soropia District Konawe Regency Southeast Sulawesi - Lufiati, Lufiati; Irawati, Irawati; Takwir, Amadhan (Jurnal Laut Khatulistiwa, 2026)
This study aims to analyze sediment types based on the grain size distribution of sand and gravel fractions and to determine sedimentation rates in the waters of Tapulaga, Konawe Regency, Southeast Sulawesi. This coastal area is influenced by ocean currents, rainfall, and anthropogenic activities associated with sedimentation processes. The research method included sediment sampling using sediment traps for 14 days at five observation stations. Sediment type and grain size were analyzed using granulometric methods through dry sieving, focusing on sand and gravel fractions. Current velocity data were obtained through direct field measurements using a current drogue, while rainfall data were obtained from the BMKG. Data were analyzed descriptively to characterize sedimentation conditions and the aquatic environment. The results showed that sediments were dominated by medium sand and gravel. The average sedimentation rate was 0.0082 g/cm²/day, with the highest value of 0.0163 g/cm²/day at Station I and the lowest value of 0.0031 g/cm²/day at Station IV. Current velocities were categorized as very slow, ranging from 0.0151 to 0.0631 m/s, while rainfall during the study ranged from light to moderate. Variations in environmental conditions indicate a relationship with sedimentation processes, which were generally relatively low.